Sensor Communication Interfaces and Standards - Viegas, Vítor (2020)
The chapter talks about the interfaces used to communicate with sensors and the standards available to channel data to higher logical levels. These communication interfaces and standards aim at abstracting the sensor layer in order to achieve interoperability at the layers above. Two standards are covered in detail: the IEEE 1451 standard that defines a smart transducer interface for sensors and actuators, and the Open Process Control (OPC) platform. The first one is an ongoing work with academic roots, while the second one is an industry-born platform. Both solutions are described in terms of architecture and internal structure, and are criticized in terms of pros and cons.